PAPP-A: A New Anti-Aging Target? - Conover, Cheryl A. (2010)
This article focuses on the role of PAPP-A in mammalian aging. It introduces PAPP-A and a little of its history, briefly discusses the function of PAPP-A in the insulin-like growth factor (IGF) system and the regulators of PAPP-A expression, and then reviews data concerning PAPP-A in aging and age-related diseases especially in regard to the PAPP-A knock-out (KO) mouse. The PAPP-A KO mouse is a valuable new model to test hypotheses concerning the control of the tissue availability of IGF, independent from systemic levels, on healthspan as well as lifespan.